Presence of Microplastics and Additives Detected in Digestive Systems of Freshwater and Saltwater Fish Consumed by Humans in Puebla, Mexico - Palma, Guadalupe Posadas-; Castañeda-Antonio, Ma. Dolores; Portillo-Reyes, Roberto; Muñoz-Rojas, Jesús; Báez, Antonino; Santamaría-Juárez, Juana Deisy; Ramírez Guzmán, Martha Elva; Rivera, Antonio (Asian Journal of Biological and Life Sciences, 2024)
Aim: This study demonstrates the presence of microplastics and associated compounds in fish consumed in Puebla a state in Mexico. Background: When plastics are improperly disposed of, they easily reach bodies of water, where they break down into tiny pieces called Micro Plastics (MPs), causing a serious environmental problem. Materials and Methods: Samples were taken from freshwater fish: rainbow trout (Oncorhynchus mykiss) and eurasian carp (Cyprinus carpio) from fish farms, as well as from marine fish: grey mullet (Mugil cephalus) and marine tilapia (Oreochromis spp) purchased from the local market. The intestinal contents were examined using three detection techniques: density separation, stereoscopic microscopy, and gas chromatography/ mass spectrometry. Results: It was found that 46.3% of the microplastic particles were black, and 85.8% of the totals were fibers. The predominant plastic was Polyethylene Terephthalate (PETE), with a total average abundance of 5.2±1.1 MPs per individual, and plastic additives, primarily phthalic acid, were detected, attributed to various anthropogenic sources contaminating the ocean. Conclusion: Consumption of freshwater fish is recommended due to their lower levels of microplastics and additive compounds.
Keywords: Fish; microplastic; pollution; waste